Stress and arterial hypertension: ISIAH rat strain - Ye. V. Antonov; Yu. V. Alexandrovich; A. A. Seryapina; L. O. Klimov; A. L. Markel (Вавиловский журнал генетики и селекции)
The main views of the issue of stress and hypertension are briefly reviewed. It is well known that stress is one of the major risk factors for cardiovascular disease development. Increase in blood pressure is a typical manifestation of the acute stress response. This fact is the reason to hypothesize that chronic stress causes the development of hypertensive disease. An association of hypertension with psychological stress in humans was shown in several works. In addition, it was demonstrated that hypertension was accompanied by an increase in sympathetic tone. On the other hand, there were many population studies in which no association was found between different types of chronic stress and arterial hypertension. Thus, the question is far from being answered. Even in the cases when one managed to obtain a significant hypertensive effect in experimental studies with emotional stress, it was difficult to explain the mechanisms mediating the formation of stressinduced hypertension. To clarify the situation, one of the authors of this review decided to begin the breeding of a rat strain with increased blood pressure response to emotional stress. This breeding gave rise to inbred rats with persistent stress-induced arterial hypertension. A brief history of the development of the genetic model ofstress-induced arterial hypertension, the ISIAH rat strain, is given. A retrospective review of the studies performed with ISIAH rats is presented. The contribution of genotype changes in the neuroendocrine systems involved in stress and blood pressure regulation to the development ofstress-dependent hypertension in the ISIAH rat strain is shown.